Про деякі змістовні процесуальні особливості протидії злочинності у місцях позбавлення волі - Карпенко, Н.; Karpenko, N. (Східноєвропейський національний університет імені Лесі Українки, 2015)
В статті розглянуті питання, що пов’язані з протидією розслідуванню злочинів, яка здійснюється організованими злочинними угрупуваннями у виправних колоніях України. Автори визначили протидію організованих злочинних формувань у виправних колоніях як комплекс різноманітних заходів легального та конспіративного характеру, що вчиняються об’єднаними у злочинні співтовариства засудженими, які відбувають покарання, для створення перешкод у розслідуванні злочинів, вчинених у цих установах виконання покарань та в цілому для негативного впливу на стан оперативної обстановки і управління процесами виконання і відбування покарання. За результатами дослідження були запропоновані науково обґрунтовані заходи щодо запобігання і нейтралізації цього суспільно небезпечного явища. In the article the questions concerning counteraction to investigation of crimes which are committed by organized criminal associations in correctional penal colonies of Ukraine have been considered and also science-based measures for preventing and neutralizing this socially dangerous phenomenon have been offered. Counteraction of organized criminal formations in correctional penal colonies should be understood as the complex of various actions of legal and secret character made by united criminal societies of convicts, serving time for this crime, for creation of hindrances in investigation of the crimes committed in these establishments of execution of punishments, and in general for negative influence on a condition of an operational situation and management of processes of execution and serving of this punishment. Counteraction tactic, which is applied by organized criminal groups in correctional penal colonies, is based on such actions, as: a) actions on the organization of criminal activity in these colonies; b) measures aimed to collect the relevant information for planning of crimes; c) the measures providing disguising of criminal activity in correctional penal colonies; d) the actions directed to creation of effective systems of contacts in structures of administration of correctional penal colonies; e) the actions directed to occupation of the real power over convicts in correctional penal colonies; e) power impact on the number of convicts who respect law and order in imprisonment places; e) criminal intelligence activity that is the main weapon in counteraction to investigation of the crimes committed in correctional penal colonies.
About Some Essential Procedural Features of Counteraction of Crime in Imprisonment Places
Keywords: протидія; розслідування злочинів; організовані злочинні угрупування; виправна колонія; запобігання злочинам; засуджений; кримінально-процесуальне законодавство; counteraction; investigation of crimes; organized criminal associations; correctional penal colony; prevention of crimes; convict; criminal and executive legislation